Feminism in Poetry During the Abbasid Era: The Representation of Women in the Poem Quluubu An-Nisaai Sakhurun by Abbas bin Ahnaf - Muslimah, Anisa Siti; Muhlisin, Mumu; Wiwaha, Rizzaldy Satria; Mostafa, Mohamed Abd El Motaleb; Rusmana, Dadan (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2025)
This study aims to analyze feminist values in literature during the Abbasid era, particularly in the representation of women in the poem